2020
DOI: 10.1016/j.phrs.2019.104514
|View full text |Cite
|
Sign up to set email alerts
|

Sex-differences in factors and outcomes associated with adherence to statin therapy in primary care: Need for customisation strategies

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 61 publications
3
30
0
2
Order By: Relevance
“…In the multivariable logistic regression models, female sex was associated with medication adherence according to MARS-5, while male sex and younger age were associated with medication adherence based on data from SPDR. Several large studies and meta-analyses have shown that female patients are consistently more likely to be non-adherent to statin therapy and other cardiovascular long-term therapies when assessed with objective assessments [ 44 47 ]. However, in a validation study of MARS-5, female sex was associated with higher MARS-5, as well as a more objective assessment with medication possession rate [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the multivariable logistic regression models, female sex was associated with medication adherence according to MARS-5, while male sex and younger age were associated with medication adherence based on data from SPDR. Several large studies and meta-analyses have shown that female patients are consistently more likely to be non-adherent to statin therapy and other cardiovascular long-term therapies when assessed with objective assessments [ 44 47 ]. However, in a validation study of MARS-5, female sex was associated with higher MARS-5, as well as a more objective assessment with medication possession rate [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This negative association between previous statin use and hearing impairment in men could be attributed to the higher rate of cardiovascular risk factors, including cardiovascular diseases, obesity, and smoking, in men than in women. In addition, sex differences in adherence to statin medication might affect the association of previous statin use with hearing impairments 31 . It was reported that women showed lower compliance with statin medication than men 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sex differences in adherence to statin medication might affect the association of previous statin use with hearing impairments 31 . It was reported that women showed lower compliance with statin medication than men 31 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis of trial conducted by Iwere and Hewitt [ 30 ] suggested that the risk of myopathy and rhabdomyolysis was not significantly different in the same age groups, regardless of whether they were exposed to statin monotherapy or a placebo. Thus, it is possible that the reduction in risk we observed in elderly depends on the fact that these patients, characterized by comorbidities and by a worse pathological status, are more aware of the importance of the therapy [ 31 ] and less prone to report SAMS. Also, it is possible that the potential of drug–drug interactions in this poly‐treated population leads the physicians to use a lower starting statin dose in older patients, as also recommended by recent guidelines [ 15 ], contributing to the results observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the regression model (Fig. 2), women and subjects who were engaged in regular physical activity were more likely to report 31.5% of all patients reporting SAMS and 3.01% of the whole PROSISA cohort (Fig. 3).…”
Section: Reported Samsmentioning
confidence: 99%